The Alleged Jesuit-Led Rebellion in 1606: Missionary Conditions in Early Seventeenth- Century China - Xie, Jingzhen (Mission studies, 2024)
In early 1606, the Chinese in Guangdong Province mobilized militarily upon learning that the Jesuits in Macau were rising up in an attempt to occupy China. However, the incident did not develop into persecution of the missionaries and was quickly put to an end with the restoration of the Jesuits’ innocence. The peaceful resolution of the alleged Jesuit-led rebellion shed new light on the rich yet complex missionary conditions in early seventeenth-century China. During this period, the Ming Dynasty was in decline, but its loyal statesmen were eager to rejuvenate Confucian values. This article argues that there were various factors contributing to the favorable atmosphere around the missionary work, including the Valignano-Ricci policy, the support provided by reliable Chinese Jesuits, the friendship and brotherhood that the Jesuits formed with Chinese scholar-officials, Ming statesmen’s various aspirations, and Ming China’s conciliatory policy toward the Portuguese in Macau.